An evaluation of the effectiveness and cost effectiveness of the National Exercise Referral Scheme in Wales, UK: a randomised controlled trial of a public health policy initiative. Issue 8 (10th May 2012) - Murphy, Simon Mark; Edwards, Rhiannon Tudor; Williams, Nefyn; Raisanen, Larry; Moore, Graham; Linck, Pat; Hounsome, Natalia; Din, Nafees Ud; Moore, Laurence
Abstract : Background: The Wales National Exercise Referral Scheme (NERS) is a 16-week programme including motivational interviewing, goal setting and relapse prevention. Method: A pragmatic randomised controlled trial with nested economic evaluation of 2160 inactive participants with coronary heart disease risk (CHD, 1559, 72%), mild to moderate depression, anxiety or stress (79, 4%) or both (522, 24%) randomised to receive (1) NERS or (2) normal care and brief written information. Outcome measures at 12 months included the 7-day physical activity recall, the hospital anxiety and depression scale. Results: Ordinal regression identified increased physical activity among those randomised to NERS compared with those receiving normal care in all participants (OR 1.19, 95% CI 0.99 to 1.43), and among those referred for CHD only (OR 1.29, 95% CI 1.04 to 1.60). For those referred for mental health reason alone, or in combination with CHD, there were significantly lower levels of anxiety (OR −1.56, 95% CI −2.75 to −0.38) and depression (OR −1.39, 95% CI −2.60 to −0.18), but no effect on physical activity. The base-case incremental cost-effectiveness ratio was £12 111 per quality adjusted life year, falling to £9741 if participants were to contribute £2 per session. Conclusions: NERS was effective in increasing physical activity among those referred for CHD risk only. Among mental health referrals, NERS did not influence physical activity but was associated with reduced anxiety and depression. Effects were dependent on adherence. NERS is likely to be cost effective with respect to prevailing payer thresholds. Trial registration: Current Controlled Trials ISRCTN47680448 .